Colloidal shuttles for programmable cargo transport. Issue 1 (December 2017) - Demirörs, Ahmet; Eichenseher, Fritz; Loessner, Martin; Studart, André
Abstract The active transport of cargo molecules within cells is essential for life. Developing synthetic strategies for cargo control in living or inanimate thermal systems could lead to powerful tools to manipulate chemical gradients at the microscale and thus drive processes out of equilibrium to realize work. Here we demonstrate a colloidal analog of the complex biological shuttles responsible for molecular trafficking in cells. Our colloidal shuttles consist of magneto-dielectric particles that are loaded with cargo particles or living cells through size-selective dielectrophoretic trapping using electrical fields. The loaded colloidal shuttle can be transported with magnetic field gradients before cargo is released at the target location by switching off the electrical field. Such spatiotemporal control over the distribution of chemically active cargo in a reversible fashion can be potentially exploited for fundamental biological research or for the development of novel technologies for advanced cell culturing, drug discovery and medical diagnosis. Biological shuttles efficiently traffic molecules in cells, inspiring the development of synthetic analogs. Here, the authors create colloidal shuttles that collect, transport, and deliver cargo particles and cells under the control of external electrical and magnetic fields.